The complete chloroplast genome sequence of Camellia sinensis var. sinensis cultivar Tieguanyin (Theaceae) - Shuai Chen; Ruoyu Li; Yaying Ma; Siru Lei; Ray Ming; Xingtan Zhang (Mitochondrial DNA. Part B. Resources, 2021)
Camellia sinensis var. sinensis cultivar Tieguanyin (TGY) is an important Oolong tea variety in China. In this study, we reported a complete chloroplast (cp) genome based on the Illumina sequencing technology and combined de novo and reference-guided assembly strategies. The complete cp genome of ‘TGY’ displayed the regular quadripartite structure: a total of 157,126 bp in length, comprising a large single-copy (LSC, 86,904 bp) region, a small single-copy (SSC, 18,532 bp) region, and a pair of inverted repeats (IRs, 26,095 bp) regions. A lot of 132 predicted genes, including 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content is 37.3%. Maximum likelihood (ML) phylogenetic tree involving 18 cp genomes of the Camellia genus revealed a relatively independent event of local domestication among three types of cultivars. The complete cp genome of ‘TGY’ provides an insight into tea plants for further understanding evolutionary research on tea plants.